Synthesis and Characterization of Heterocyclic Compounds Derived From 4- Hydroxy and 4-Amino Acetophenone - Karam, Nisreen H.; Tomma, Jumbad H.; AL-dujaili, Ammar H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Two series of Schiff Bases [VI]n and thiazolidin-4-one derivatives[VII]n were synthesized by many steps starting from cyclization of 4- hydroxyacetophenon with thiourea in iodine to yield 1,3-thiazole compound which was reacted with pentoxy bromide in anhydrous potassium carbonate to converted compound[II] and this reacted with Phenol to yield azo compound[III]. The azo compound reacted with ethyl chloro acetate in basic medium to get a new easter compound[IV]  which is converted to their acid hydrazid[V]. The later compound condensation with n-alkoxy benzaldehyde to give new Schiff bases[VI]n . Imine group undergoes addition cyclization with thioglycolic acid to get thiazolidinone compounds[VII]n .Also, two new series of Schiff Bases [XII]n and their thiazolidin-4-one derivatives[XIII]n were synthesized by using the same steps given for synthesis Schiff bases [VI]n and thiazoidinone [VII]n except using  4- aminoacetophenon instead of 4- hydroxyacetophenon(see scheme 2) .The synthesized compounds were characterized by melting points , FTIR ,C.H.N.S analysis , 1HNMR  and Mass spectroscopy (of some of them)